Correlation Analyses of Clinical Manifestations and Variant Effects in KCNB1-Related Neurodevelopmental Disorder - Xiong, Juan; Liu, Zhonghua; Chen, Shimeng; Kessi, Miriam; Chen, Baiyu; Duan, Haolin; Deng, Xiaolu; Yang, Lifen; Peng, Jing; Yin, Fei (Frontiers in Pediatrics, 2022)
Objective: “Complete or partial loss of function (LoF)” and “dominant-negative (DN) effect” are adopted to describe variants’ molecular phenotypes in KCNB1-related neurodevelopmental disorder. We aimed to investigate clinical presentations and variant effects associations in the condition. Methods: We reported 10 Chinese pediatric patients with KCNB1-related neurodevelopmental disorder here. Functional experiments on newly reported variants including electrophysiology and protein expression were performed in vitro. Phenotypic, functional, and genetic data in the cohort and published literature were collected. According to their variants’ molecular phenotypes, patients were grouped into complete or partial LoF, and DN effect or non-dominant-negative (non-DN) effect to compare their clinical features. Results: Nine causative KCNB1 variants in 10 patients were identified, including 8 novel and 1 reported. Epilepsy, global developmental delay and behavior issues were their common clinical features. Functional analyses revealed 3 partial and 5 complete LoF variants, 5 DN and 3 non-DN effect variants. Patient 1 in our series with truncated variants with haploinsufficiency had the best prognosis. Patients in complete LoF group had earlier seizure onset age (64.3% vs 16.7%, p=0.01) and worse seizure outcomes (18.8% vs 66.7%, p=0.03), and patients in DN effect subgroup had multiple seizure types (65.5% vs 30.8%, p=0.039). Conclusion: Patients with KCNB1 variants in the Asian cohort have similar clinical manifestations to those of other races. Truncated variants exhibiting with haploinsufficiency molecular phenotype, are linked to milder phenotypes. Cases with complete LoF and DN effect KCNB1 variants have more severe epilepsy.